Does a quality management system improve quality in primary care practices in Switzerland?: a longitudinal study - Götz, Katja; Hess, Sigrid; Jossen, Marianne; Huber, Felix; Rosemann, Thomas; Brodowski, Marc; Künzi, Beat; Szecsenyi, Joachim (BMJ open, 2015)
Objectives: To examine the effectiveness of the quality management programme—European Practice Assessment—in primary care in Switzerland. Design: Longitudinal study with three points of measurement. Setting: Primary care practices in Switzerland. Participants: In total, 45 of 91 primary care practices completed European Practice Assessment three times. Outcomes: The interval between each assessment was around 36 months. A variance analyses for repeated measurements were performed for all 129 quality indicators from the domains: ‘infrastructure’, ‘information’, ‘finance’, and ‘quality and safety’ to examine changes over time. Results: Significant improvements were found in three of four domains: ‘quality and safety’ (F=22.81, p<0.01), ‘information’ (F=27.901, p<0.01) and ‘finance’ (F=4.073, p<0.02). The 129 quality indicators showed a significant improvement within the three points of measurement (F=33.864, p<0.01). Conclusions: The European Practice Assessment for primary care practices thus provides a functioning quality management programme, focusing on the sustainable improvement of structural and organisational aspects to promote high quality of primary care. The implementation of a quality management system which also includes a continuous improvement process would give added value to provide good care.
Gesehen am 29.06.2020